The importance of emotional intelligence for the sales associates profession as a mediation between job stress and job satisfaction - Christine Winstinindah Sandroto; Jessica Fransiska (International Journal of Management and Economics, 2021)
Sales associates need emotional intelligence (EI) in dealing with job stress and perceived job satisfaction. So far, there has been no research that explains the effect of job stress on job satisfaction with EI as a mediating variable in the sales associate profession. This study examines EI's role in managing job stress allows sales associates to achieve job satisfaction. The population in this study is comprised of sales associates in Jakarta-Indonesia, who work in malls that target middle to upper-class level customers, with a sample size of 100 respondents. The sampling technique used was accidental sampling; the analysis uses the simple mediation model with the macro process through SPSS process 22.0 for Windows using ordinary least squares and logistic regression path analysis modeling. The finding reveals that the higher the level of EI, the stronger the extent to which the relationship between job stress and job satisfaction is mediated.
Keywords: D23; L84; M53; O15; 650; emotional intelligence; job satisfaction; job stress; sales associate